Policy, Leadership Style, Organizational Culture, Citizen’s Participation on Service Quality in South Tangerang’s Disdukcapil - Tangkilisan, Gunawan; Adiwisastra, Josy; Hubeis, Musa; Sulistyani, Dewi (International Journal Labs, 2022)
The implementation of policies, leadership styles, organizational culture, and community participation has not been maximal in providing encouragement or can influence the employees of the Population and Civil Registration Service (Disdukcapil) and the community to implement various policies directly related to population and civil registration. This study aims to analyze the effect of policy implementation, leadership style, organizational culture and community participation on the service quality of the Disdukcapil in South Tangerang, Banten. This study uses a quantitative method with explanatory research type, with a population of 2,164 and a research sample of 216 people. The sampling technique used is simple random sampling where the sample is taken randomly. While the data analysis method used in this research is simple linear regression analysis and multiple linear regression analysis. There is a positive and significant effect of policy implementation on service quality by 83.8%, leadership style to service quality by 78.7% organizational culture to service quality by 75.6%, and community participation on service quality by 90.7%. While the joint implementation of policies, leadership, organizational culture, and community participation have a positive and significant impact on the service quality of Disdukcapil in South Tangerang by 96.6%. So that in the future, the service of Disdukcapil should pay attention to the importance of policy implementation factors, leadership styles, organizational culture, and community participation in the implementation of service quality so that it can run better to the community, especially in the field of population and civilians registration that are still not optimal.